TiM: Ti i Muzej (Team: You and Museum) - Miličić, Dolores (Array, 2013)
This paper describes a collaborative service learning project between students of Information Sciences from the Faculty of Humanities and Social Sciences, Museum of Arts and Crafts and elementary school “Cvjetno naselje” and presents the outcomes of this affiliation. Students of information sciences gained practical experience working with the museum pedagogue and leading school classes through the Museum, while the Museum gained young experts and valuable help in its outreach mission. Positive responses from all partners promoted future partnerships between the Faculty’s students and the Museum. Project evaluation addressed the role of field experiences in student education, museum education partnerships and service learning pedagogy.